1994
DOI: 10.1063/1.358395
|View full text |Cite
|
Sign up to set email alerts
|

Detailed analysis of carrier transport in InAs0.3Sb0.7 layers grown on GaAs substrates by metalorganic chemical-vapor deposition

Abstract: InAs0.3Sb0.7 layers with mirrorlike morphology have been grown on GaAs substrates by low-pressure metalorganic chemical vapor deposition. A room-temperature electron Hall mobility of 2×104 cm2/V s has been obtained for a 2-μm-thick layer. Low-temperature resistivity of the layers depended on TMIn flow rate and layer thickness. Hall mobility decreased monotonically with decreasing temperature below 300 K. A 77 K conductivity profile has shown an anomalous increase in the sample conductivity with decreasing thic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
18
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 32 publications
5
18
0
Order By: Relevance
“…The data in Table 2 show that sample F exhibits better quality than sample D, suggesting that growth conditions still have a pronounced influence on material quality even though the epitaxial conditions are already met. The Hall mobilities of the samples are all relatively low compared with those grown by MBE [8,10] and MOCVD [12]. Considering the high carrier concentrations (410 18 cm À3 ) in the samples, it should be mainly attributed to the impurities unintentionally but heavily doped to the InAs 0.3 Sb 0.7 films.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The data in Table 2 show that sample F exhibits better quality than sample D, suggesting that growth conditions still have a pronounced influence on material quality even though the epitaxial conditions are already met. The Hall mobilities of the samples are all relatively low compared with those grown by MBE [8,10] and MOCVD [12]. Considering the high carrier concentrations (410 18 cm À3 ) in the samples, it should be mainly attributed to the impurities unintentionally but heavily doped to the InAs 0.3 Sb 0.7 films.…”
Section: Resultsmentioning
confidence: 99%
“…It can be inferred that the threshold value of growth rate lies on the diffusion speed of the atoms absorbed on the substrate surface. Note that by MBE [8,10] or MOCVD [2,12] can be achieved at the substrate temperature range of 400-480 1C, and one could see some differences in growth mechanism between magnetron sputtering and MBE or MOCVD. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies of strained InAs grown on GaAs and Si substrates [10][11][12][13][14] have shown that the deposited layer may be separated into three regions: the interface, the bulk, and the surface. The extent of the interface layer varies with different growth conditions and especially with various attempts to reduce the dislocation density where it can be reduced from 1 m ͑Ref.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of dislocations on the electrical conduction in GaAs-based compounds has been widely investigated [2][3][4][5][6][7][8][9][10][11][12]. However, skew scattering has not been taken into account.…”
Section: Introductionmentioning
confidence: 99%